2018
DOI: 10.1001/jamadermatol.2018.1768
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Scope of Dermatology Procedures Billed by Advanced Practice Professionals From 2012 Through 2015

Abstract: idlevel or advanced practiced professionals (APPs) such as nurse practitioners (NPs) and physician assistants (PAs) are often employed in specialty offices to extend access to care. Coldiron and Ratnarathorn 1 demonstrated that APPs also independently bill for a large number of procedures-nearly 5 million in the 2012 Medicare population, 55% of which were dermatologic. In this study, we examine how the scope and number of dermatologic procedures performed by APPs have continued to evolve from 2012 through 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
(18 reference statements)
2
13
0
Order By: Relevance
“…Dermatology practice ownership by PE firms has been demonstrated to be associated with increased hiring of NPCs, and hypothesized to lead to an increased likelihood that these clinicians do not receive adequate supervision from the physicians who oversee them . While use of NPCs has broadly increased over time in dermatology clinics of varied practice type and geography, our results based on directly inquiring about clinician availability demonstrated that PE-owned clinics were more likely to offer appointments with NPCs than their geographically matched controls, a finding consistent with a recent study analyzing clinician use at PE-owned clinics …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Dermatology practice ownership by PE firms has been demonstrated to be associated with increased hiring of NPCs, and hypothesized to lead to an increased likelihood that these clinicians do not receive adequate supervision from the physicians who oversee them . While use of NPCs has broadly increased over time in dermatology clinics of varied practice type and geography, our results based on directly inquiring about clinician availability demonstrated that PE-owned clinics were more likely to offer appointments with NPCs than their geographically matched controls, a finding consistent with a recent study analyzing clinician use at PE-owned clinics …”
Section: Discussionsupporting
confidence: 88%
“…Private equity firms invest in dermatology practices and aim to enhance their financial performance, causing physicians to express concern that the fiduciary responsibility of PE firms may incentivize operational changes at dermatology practices that jeopardize access to or reduce the quality of care for patients . This can include increasing use of NPCs, whose reduced salaries and increased performance of billable procedures would benefit the financial goals of these firms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Despite the lack of formalized dermatologic training, APPs billed for 13.4% of all dermatology procedures submitted to Medicare in 2015. 12 Quality of Patient Care-In our study, physicians also voiced concern over reduced quality of patient care. In a review of 33,647 skin cancer screening examinations, PAs biopsied an average of 39.4 skin lesions, while dermatologists biopsied an average of 25.4 skin lesions to diagnose 1 case of melanoma.…”
Section: Commentmentioning
confidence: 88%
“…1 Subsequent studies have documented further expansion of procedures billed independently by NPPs in dermatology, but a paucity of data exists documenting NPP billing trends in dermatology beyond 2016. 2–4 This study explored NPP billing trends within procedural dermatology in the Medicare population from 2016 to 2019 to assess whether these trends mirrored billing in years before 2016.…”
mentioning
confidence: 99%